Doppler ultrasound and the silent ductus arteriosus. Issue 2 (February 1991) - Houston, A B; Gnanapragasam, J P; Lim, M K; Doig, W B; Coleman, E N
Abstract : A clinically undetectable, small ductus arteriosus was identified by Doppler ultrasonography in 21 individuals. Infants were excluded from the study and no patient had pulmonary hypertension. Persistence of the ductus arteriosus is likely to be more common than shown by less sensitive diagnostic methods. Some patients considered to have infective endocarditis with a normal heart may have a silent ductus arteriosus. Evidence of such an association would justify ligation or antibiotic cover as prophylactic measures.